Optimasi dan Evaluasi Mikroemulsi Minyak Prepupa Black Soldier Fly (Hermetia illucens) - Adhitya Jessica; Erizal Zaini; Nabila Maulidya Khairunnisa (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Hermetia illucens, commonly known as the Black Soldier Fly (BSF), is an insect rich in fatty acids and has potential for use as an active cosmetic ingredient, particularly for anti-aging applications. To ensure stability and achieve optimal efficacy, BSF prepupal oil was formulated into a microemulsion system. This study aimed to optimize the microemulsion formulation of BSF prepupal oil using a combination of Tween 80 as a surfactant and PEG 400, Pluronic 127, and ethanol as candidate of cosurfactants, and to evaluate its physicochemical characteristics and stability. The formulation process began with the selection of an appropriate surfactant–cosurfactant combination, followed by optimization of the selected surfactant–cosurfactant concentrations using the Simple Lattice Design method in Design Expert® 13 software. The optimized formulations were then evaluated for organoleptic properties, pH, viscosity, transmittance, globule size, and stability through temperature cycling and centrifugation tests. The results showed that the combination of Tween 80 and PEG 400 produced a stable microemulsion with high clarity. The optimal formulation (F12) consisted of 55.56% Tween 80, 22.22% PEG 400, and 11.11% BSF prepupal oil, exhibiting a transmittance of 98.30 ± 0.26%, a pH range of 5.19–5.70, a viscosity of 375 ± 0.54 cP, and a globule size of 550.71 ± 0.32 nm. This formulation remained stable under thermal stress and accelerated centrifugation without phase separation. Based on these findings, BSF prepupal oil can be effectively formulated into a stable microemulsion and shows potential for further development as an active cosmetic ingredient.